ANALYSIS OF THE HUMAN DEVELOPMENT INDEX AND FACTORS AFFECTING IT IN EASTERN INDONESIA - Sri Rahmah Wafitrah; Rahmatia Rahmatia; Nur Dwiana Sari Saudi (Jurnal Ekonomi, 2023)
This study aims to measure and analyze the effect of government spending on education, government spending on health, government spending on social protection, investment, and an educated workforce on the human development index in eastern Indonesia, both directly and indirectly through economic growth. This study uses panel data with 17 cross sections over a 5 year time series , from 2015 to 2019. The analytical method used is the structural equation method. The results of the study show that government spending on education does not have a direct effect on the human development index, while government spending on health, investment and an educated workforce has a positive effect. Meanwhile, government spending on social protection has a negative effect. Meanwhile, the indirect effect of all exogenous variables through economic growth is stated to have no effect. This is due to the absence of the influence of economic growth on the human development index. The most dominant influence on the human development index is from an educated workforce, so the government needs to focus more on educating the entire community to create superior and competitive human resources. Superior human resources are directly proportional to income which will increase so that a decent standard of living can be met, because the most important thing in the entire development process is the people themselves.